Enhancing the efficacy of traditional Mongolian alcohol-spraying bone-setting therapy for surgical neck fractures of the humerus: the effects and mechanisms of muscular origin-insertion point massage therapy - Xie, Changjiang; Du, Mengte; Wang, Xin; Xi, Huqitu; Wei, Tianhu (Frontiers in Surgery, 2026)
BackgroundHumeral surgical neck fractures (HSNF) are among the most common shoulder fractures, yet their treatment outcomes remain variable. Clinical observations suggest that combining traditional Mongolian alcohol-spraying bone-setting therapy with muscular origin-insertion point massage may accelerate fracture healing; however, the therapeutic efficacy and underlying mechanisms require further validation.MethodsA total of patients with HSNF were randomly allocated into two groups. The control group received Mongolian alcohol-spraying bone-setting therapy, while the experimental group received the same treatment plus muscular origin-insertion point massage. Clinical outcomes were assessed using the Constant-Murley and Neer shoulder function scores at multiple time points. To explore potential mechanisms, serum levels of soluble intercellular adhesion molecule-1 (sICAM-1), soluble vascular cell adhesion molecule-1 (sVCAM-1), platelet-derived growth factor (PDGF), insulin-like growth factor-1 (IGF-1), and hemorheological parameters (erythrocyte aggregation index, plasma viscosity) were measured.ResultsFrom four weeks post-treatment onward, the experimental group exhibited significantly higher Constant-Murley and Neer scores compared with the control group (p < 0.05). Biochemical analysis showed that serum sICAM-1 was significantly lower in the experimental group beginning at two weeks (p = 0.02), whereas sVCAM-1 was reduced from four weeks (p < 0.01). In contrast, PDGF (p = 0.03) and IGF-1 (p = 0.04) were significantly elevated from four weeks onward in the experimental group. Moreover, erythrocyte aggregation index (p = 0.02) and plasma viscosity (p = 0.04) were significantly lower in the experimental group from four weeks post-treatment.ConclusionThe combination of muscular origin-insertion point massage with Mongolian alcohol-spraying bone-setting therapy yields favorable clinical outcomes, potentially by alleviating local inflammation and enhancing microcirculation, thereby promoting fracture healing. This integrative approach may represent a promising therapeutic strategy for the management of HSNF.